SOFTWARE PACKAGE FOR SOLVING THE PROBLEMS OF ANALYSIS AND SYNTHESIS OF NETWORKED CONTROL SYSTEMS - A. E. Emelyanov (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2015)
Summary. Modern control systems shall exchange data packets through the network channels. Such systems are called network management systems. One of the promising directions of development of network management systems is the use of common computer networks in the control loop for the exchange of information between elements of the system. Such a construction of control systems leads to new problems. So in the design and study of such systems need to combine different methods of scientific fields. First of all, it is the field of control theory and communication theory. However, not all the developer has full knowledge of these areas to the same extent. To solve engineering problems, in order to ensure the required quality of operation, developed methods of analysis and synthesis of networked control systems with data transmission over a channel with competing access methods. These techniques allow the calculation of probability-time characteristics of a stochastic process data channel with competing access methods to build transients considered control systems to calculate their qualitative characteristics, to determine the conditions of stability of network systems management and tuning parameters to optimize the digital controllers for the respective criterion. These techniques are the basis for the development of software. The proposed software system allows for the analysis and synthesis of the network through which the information data exchange. As well as to study the network system for a variety of laws regulation. Complex structure based on the principles of modularity, hierarchy and nesting modules to each other. Easy to use interface allows the software user numb special training.